Resolutions, adopted by the "convention of the people," at Metropolitan Hall, in the city of Richmond, April 18, 1861 - French, S. Bassett, (Samuel Bassett) 1820-1898 ([publisher not identified], 1861)
Resolutions that were adopted by the "convention of the people" that supported the Confederacy and the defense of Virginia and were signed by S. Bassett French.